Antibiotic resistance and NG-MAST sequence types of Neisseria gonorrhoeae isolates in Poland compared to the world - Młynarczyk-Bonikowska, Beata; Malejczyk, Magdalena; Majewski, Sławomir; Unemo, Magnus (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Gonorrhoea is one of the most common sexually transmitted infections and in 2012, the World Health Organization estimated about 78 million of new global urogenital cases among adults per year. The main concern during the latest decade has been the emergence and spread of multidrug-resistant strains of Neisseria gonorrhoeae. Resistance has emerged internationally to the extended-spectrum cephalosporins, ceftriaxone and cefixime, which are the last remaining options for empiric first-line monotherapy of gonorrhoea. In Poland, the levels of resistance to ciprofloxacin, benzylpenicillin and tetracycline are high, and the prevalence of azithromycin resistance has increased. However, no resistance to ceftriaxone has been identified. The currently spread multidrug-resistant strains frequently represent epidemic clones. The present paper reviews and describes the antimicrobial resistance and N. gonorrhoeae multiantigen sequence typing (NG-MAST) sequence types of N. gonorrhoeae strains spreading in Poland compared to the world.